Seismic failure behavior of masonry domes under strong ground motions. (December 2022) - Bayraktar, Alemdar; Hökelekli, Emin; Yang, Tony T.Y.
Highlights: Static and seismic behaviors of masonry domes with circular and octagonal drum and buttress. Failure behaviours of masonry domes with circular and octagonal drum and buttress under strong earthquake shaking. Failure angles of masonry domes with thickness-to-span ratios t/R = 0.092 under strong ground motions. Abstract: General stability and failure behaviors of masonry domes under static loads have been investigated extensively in literature. However, a few studies have been done on the seismic failure behavior of masonry domes under strong ground shaking. This study aims to investigate the seismic failure behaviors and failure angles of masonry domes with support system including drum and buttresses using advanced 3D nonlinear numerical simulations. Four types of masonry domes with thickness-to-span ratios t/R = 0.092, such as a dome with circular drum (Dome A), a dome with circular drum and buttress (Dome B), a dome with dodecagon drum (Dome C), a dome with dodecagon drum and buttress (Dome D), built on historical structures are selected. Three-dimensional solid finite element models of the selected masonry domes are created using isotropic continuum macro modelling technique with homogenized properties. The finite element models are utilized to simulate the seismic behaviors of the masonry domes under three different strong ground motion acceleration records matched according to the target response spectrum with a return period of 475 years in the Turkish Building Earthquake Code. The seismic failure behaviors of four masonry dome models are evaluated by comparing mode shapes, displacements, maximum principal stresses, damage propagation patterns and failure angles. It is determined that the average angle intervals of hoop tension failure regions of Dome A, Dome B, Dome C and Dome D models under strong ground motions vary between 39, 25, 35 and 26 degrees, respectively.